2013
DOI: 10.1002/app.39783
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun nylon 6 nanofibers incorporated with 2‐substitutedN‐alkylimidazoles and their silver(I) complexes for antibacterial applications

Abstract: The article presents the incorporation of biocides [2‐substituted N‐alkylimidazoles and their silver(I) complexes] into electrospun nylon 6 nanofibers for application as antimicrobial materials. The electrospun nylon 6/biocides nanofiber composites were characterized by IR spectroscopy (ATR‐FTIR) and scanning electron microscopy (SEM‐EDX). The antimicrobial activity of the electrospun nylon 6/biocides nanofiber composites was evaluated against Escherichia coli, Staphylococcus aureus, and Bacillus subtilis subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…24 Further study showed that the incorporation of the above mentioned ligands and their Ag(I) complexes into electrospun nylon 6 nanofibers produces attractive antimicrobial materials. 25 Rowan et al 20 investigated the growth of inhibitory effects of silver(I) complexes containing imidazole derivatives against the pathogenic bacteria MRSA and E. coli and the fungal pathogen C. albicans. Amongst the five investigated Ag(I)imidazole (imH) complexes, two them, i.e.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…24 Further study showed that the incorporation of the above mentioned ligands and their Ag(I) complexes into electrospun nylon 6 nanofibers produces attractive antimicrobial materials. 25 Rowan et al 20 investigated the growth of inhibitory effects of silver(I) complexes containing imidazole derivatives against the pathogenic bacteria MRSA and E. coli and the fungal pathogen C. albicans. Amongst the five investigated Ag(I)imidazole (imH) complexes, two them, i.e.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…18,19 Numerous Ag(I) complexes containing imidazole derivatives have shown significant broad spectrum antimicrobial activity. [20][21][22][23][24][25][26][27] Interestingly, although free imidazole ligands display no activity against pathogenic microorganisms, their activity increases when complexed with silver ions. The components of the silver(I) complexes probably act synergistically.…”
Section: Introductionmentioning
confidence: 99%